Investigation of organic composition of potential plants as alternative fiber in paper making industry - Mohd Hatta, Mohd Zainuri (2014)
Malaysia was known as a country that rich with a source of agro waste material. Three different crops had been studied which include the pineapple (Ananas Comosus) leaf, corn (Zea mays) stalk and Napier grass (Pennisetum purpureum). Those crops were characterized as agro waste material in Malaysia and have a high potential to become an alternative fiber. The objective of this work was to analysis the chemical composition which are pineapple leaf, corn stalk and Napier grass; to investigate the properties of hand sheet made from those crops; to determine the influence of different pulping process and process variables on the physical and chemical properties. Every chemical components analyse; Cellulose, Hemicellulose, Ash and Lignin content by TAPPI Test Method. All of three samples were undergo acidic and alkali pulping process. Fiber Analyser was used for fiber analysis and SEM use for observation on sample. From pulping process, the step will continue for papermaking. Lastly, tensile, bursting, folding, and tearing tester machine will test paper production. Result shows that pineapple leaf gives high cellulose content (66.2%) and lower lignin content (4.2%) compared corn stalk and napier grass. Alkaline pulping shows a quality of pulp rather than acidic pulping process due to the pulp strength and colour of fiber. Corn stalk gives a high potential to be an alternative for mechanical properties viewed. High tensile index (90.99 Nm/g), burst 2 index (6.64 kPa*m /g) and fold index (3.51 Nm) by corn stalk paper rather than pineapple leaf and napier grass but lower in tear index (2.85 Nm /g). This wass due to the long fiber length by pineapple leaf about 13.36 mm from SEM images. This arrangement form and effect a structure of fiber. Based on all tests, corn stalk materials have high potential to be fiber substitution but pineapple leaf and napier grass have their own characteristic to be alternative fiber. This research also promote green technology where one of the solid waste material technology for waste from agricultural residue. 2